Toxic Effects in Gaster of Rhizoma Coptidis (Huang Lian) Treated Mice using Histology Technique - Nurul Syameera, Aduka; Ai, Wen Lai (INTI International University, 2018)
The study was conducted to examine the effects of 65 mg/kg, 250 mg/kg and 500 mg/kg of Rhizoma coptidis (Huang Lian) on the changes in gastric epithelium tissue, submucosa tissue and muscularis tissue of mice. In the experiment, sample of gaster organ of control group mice, 65 mg/kg Rhizoma coptidis treated mice, 250 mg/kg Rhizoma coptidis treated mice and 500 mg/kg Rhizoma coptidis treated mice are collected. All samples are stored in 10% (v/v) neutral buffered formalin solution with pH 6.8-7.2 at 25˚C. In the first procedure, each sample underwent tissue processing and tissue sectioning. Then, data were collected by observing tissues under microscope for gross and microscopic examination. There was no significant change in gross appearance of gaster of control group, 65 mg/kg, 250 mg/kg and 500 mg/kg of Rhizoma coptidis treated mice. In additional, the microscopic examination in the gaster of 65 mg/kg and 250 mg/kg of Rhizoma coptidis treated mice, the layer of mucosa, submucosa and muscularis externa can be identified. Gastric pits can be identified clearly with no sign of erosion. However in the gaster of 500 mg/kg of Rhizoma coptidis treated mice, there were presence of black dots which indicates infiltration of inflammatory cells filling in lamina propria. There was high infiltration rate in mucosa layer indicates inflammation happens at the mucosa layer. Minor detachment of tissue in this 500 mg/kg treated mice can also be observed under microscope. It can be concluded that the gaster of 500 mg/kg of Rhizoma coptidis treated mice brings morphological changes to the tissue cells in gaster, specifically causes infiltration of inflammatory cells, and indicates that 500 mg/kg of R. coptidis carries toxic to the tissue cells at microscopic level.